The intention to receive tuberculosis preventive therapy in adult household contacts of pulmonary TB patients in Delhi, India - Nandini Sharma; Saurav Basu; Ashwani Khanna; Pragya Sharma; Shivani Chandra (Journal of Infection in Developing Countries)
Introduction: The integration of newer tuberculosis preventive therapy regimens, which have shorter treatment duration, simpler dosing requirements, and improved safety profile, is being considered within India’s national tuberculosis elimination program. However, a potential operational challenge in the successful rollout of the expanded TPT plan is the extent of its acceptability in adult household contacts of pulmonary tuberculosis patients due to possibility of lower risk perception and suboptimal perceived benefit. This study was conducted to determine the intention to accept Tuberculosis Preventive Therapy among adult household contacts of pulmonary tuberculosis patients in Delhi, India.